Atividade física na fase da meia-idade: motivos de adesão e de continuidade - Andréa Krüger Gonçalves; Cátia Pereira Duarte; Cristiane Leite dos Santos (Universidade Federal do Rio Grande do Sul, 2001)
The aim ofthis research is to identify the reasons that drive the middle-age people to the perform physical activities and to board varied points that assist in the comprehension of the attitudes (expectations, motivations, results, impediments). This study is an exploratory social investigation based in a qualitative methodology with 60 active people. The results allow the Identification of the reasons that drive people with more than four life decades (with minimum experience) practice physical activities, but more investigation is necessary about social influence and the active or sedentary behavior in different life phases.